Methods of Teaching Intercultural Communicative Competence to Students (Eurasian Journal of Learning and Academic Teaching, 2023)
This article discusses the methodology for teaching intercultural communicative competence in the process of educational translation of English texts. As well as the ability to analyze, compare, interpret the features of one's own and other linguistic communities, manifesting themselves in the professional sphere of human activity. It is about teaching intercultural professional communicative competence. The study found that intercultural professional communicative competence is formed within limited limits and the ability to intercultural communication with colleagues.